Development of an image Mean Square Displacement (iMSD)-based method as a novel approach to study the intracellular trafficking of nanoparticles - Digiacomo, Luca (Acta Biomater, 2016)
Fluorescence microscopy and spectroscopy techniques are commonly used to investigate complex and interacting biological systems (e.g. proteins and nanoparticles in living cells), since these techniques can explore intracellular dynamics with high time resolution at the nanoscale. Here we extended one of the Image Correlation Spectroscopy (ICS) methods, i.e. the image Mean Square Displacement, in order to study 2-dimensional diffusive and flow motion in confined systems, whose driving speed is uniformly distributed in a variable angular range. Although these conditions are not deeply investigated in the current literature, they can be commonly found in the intracellular trafficking of nanocarriers, which diffuse in the cytoplasm and/or may move along the cytoskeleton in different directions. The proposed approach could reveal the underlying system’s symmetry using methods derived from fluorescence correlation concepts and could recover dynamic and geometric features which are commonly done by single particle analyses. Furthermore, it improves the characterization of low-speed flow motions, when compared to SpatioTemporal Image Correlation Spectroscopy (STICS). Although we present a specific example (lipoplexes in living cells), the emphasis is in the discussion of the method, its basic assumptions and its validation on numeric simulations.